Coordination of The Constitution of The Republic of Uzbekistan With The Ideas of The Jadids Movement (Social - Philosophical Analysis) - Sobirovich, Rizayev (Indonesian Journal Publisher, 2025)
At the end of the 19th century, at the beginning of the 20th century, the Jadidism movement, the social and political actions and the ideas they promoted served as an important factor for the spiritual life of that time. The Jadidlar movement included not only educational or cultural-educational activities, but also the development of social, political and legal culture, and the creation of the conceptual foundations of civil society. In the process of adoption of the new version of the Constitution of the Republic of Uzbekistan, along with the study of the legal system of many developed countries, we can see that the views of modern intellectuals were also reflected in the changes. In this article, changes in the Constitution of the Republic of Uzbekistan are analyzed in harmony with the ideas of modernism.